Markers of Immune Activation and Inflammation in Individuals With Postacute Sequelae of Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (27th September 2021) - Peluso, Michael J; Lu, Scott; Tang, Alex F; Durstenfeld, Matthew S; Ho, Hsi-en; Goldberg, Sarah A; Forman, Carrie A; Munter, Sadie E; Hoh, Rebecca; Tai, Viva; Chenna, Ahmed; Yee, Brandon C; et al.
Abstract: Background: The biological processes associated with postacute sequelae of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (PASC) are unknown. Methods: We measured soluble markers of inflammation in a SARS-CoV-2 recovery cohort at early (<90 days) and late (>90 days) timepoints. We defined PASC as the presence of 1 or more coronavirus disease 2019 (COVID-19)–attributed symptoms beyond 90 days. We compared fold-changes in marker values between those with and without PASC using mixed-effects models with terms for PASC and early and late recovery time periods. Results: During early recovery, those who went on to develop PASC generally had higher levels of cytokine biomarkers including tumor necrosis factor–α (1.14-fold higher mean ratio [95% confidence interval CI, 1.01–1.28]; P = .028) and interferon-γ–induced protein 10 (1.28-fold higher mean ratio [95% CI, 1.01–1.62]; P = .038). Among those with PASC, there was a trend toward higher interleukin 6 levels during early recovery (1.29-fold higher mean ratio [95% CI, .98–1.70]; P = .07), which became more pronounced in late recovery (1.44-fold higher mean ratio [95% CI, 1.11–1.86]; P < .001). These differences were more pronounced among those with a greater number of PASC symptoms. Conclusions: Persistent immune activation may be associated with ongoing symptoms following COVID-19. Further characterization of these processes might identify therapeutic targets for those experiencing PASC. Abstract : Compared to individuals reporting full recovery, individuals with symptoms for >90 days following COVID-19 had subtle elevations in levels of certain markers of immune activation. Further characterization of these processes might identify therapeutic targets for those experiencing postacute sequelae of SARS-CoV-2tion.